The constraints on the power spectrum of relic gravitational waves from current observations of large-scale structure of the Universe - Novosyadlyj, B.; Apunevych, S. (Кинематика и физика небесных тел, 2005)
Within the framework of cosmological inflationary models, relic gravitational waves arise as a natural consequence of the quantum nature of primordial space-time metric fluctuations and a validity of the general theory of relativity. Therefore, the detection of cosmological gravitational waves would be the strongest evidence in support of basic assumptions of the inflation theory. Although the tracing gravitational waves by polarization patterns on last scattering surface of the cosmic microwave background is only planned for forthcoming experiments, some general constraints on the tensor mode of metric perturbations (i.e., gravitational waves) can be established right now. We present a determination of the amplitude of the relic gravitational waves power spectrum. An indirect best-fit technique was applied to compare observational data and theoretical predictions. As observations we have used data on the large-scale structure of the Universe and anisotropy of the cosmic microwave background temperature. The conventional inflationary model with 11 parameters has been investigated, all parameters were jointly evaluated. This approach gave us a possibility to find parameters of the power spectrum of gravitational waves along with statistical errors.